Identifying Strengths and Challenges in Interdisciplinary Graduate Supervision - Hibbert, Kathy; Lingard, Lorelei; Pitman, Alan; Kinsella, Anne; Wilson, Tim; McKenzie, Pamela J.; Vanstone, Meredith; Masinire, Alfred (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This poster introduces the methodology and presents preliminary results from a pilot study of faculty, student, and administrator perspectives on graduate supervision in an interdisciplinary environment. The research team surveyed doctoral students and conducted in-depth interviews, focus groups, and reflective exercises with graduate students and faculty at one Canadian university. Cette affiche présente la méthodologie et les résultats préliminaires d’une étude pilote auprès de professeurs, d’étudiants et d’administrateurs quant à leurs perspectives sur la supervision d’étudiants en contexte interdisciplinaire. Les chercheurs ont sondé des doctorants et ont mené des entrevues en profondeur, des groupes de discussion et des exercices de réflexion avec des étudiants et des professeurs d’une université canadienne.